2022
DOI: 10.54386/jam.v16i1.1493
|View full text |Cite
|
Sign up to set email alerts
|

Study on change in microenvironment under different colour shade nets and its impact on yield of spinach (Spinacia oleracea L.)

Abstract: Field experiment was undertaken at research farm of IARI, New Delhi to study the effect of change in the microenvironment under different colour shade nets during summer and rainy season, of 2012 on yield of spinach. Spinach crop was sown under different colour shade nets such as red, green, black, white along with control (without shade net) during summer and rainy season. Crop duration from sowing to harvesting was 62 days in summer and 58 days in rainy season. Different weather parameters were measured at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Gaurav et al (2016) found that the DLI was greater under white shade than under red or black shade. Similarly, Meena et al (2014) found that the photosynthetic photon flux was greatest under pearl shade than under red, green, or black shade. Air temperature was greatest under red shade and lowest under aluminet shade at 31.3 C and 29.7 C, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…Gaurav et al (2016) found that the DLI was greater under white shade than under red or black shade. Similarly, Meena et al (2014) found that the photosynthetic photon flux was greatest under pearl shade than under red, green, or black shade. Air temperature was greatest under red shade and lowest under aluminet shade at 31.3 C and 29.7 C, respectively.…”
Section: Resultsmentioning
confidence: 82%
“…The minimum (4.04 t/ha) fruit yield was found in the Control which was statistically at par with all other treatments. High amount of nitrogen and organic carbon present in Goat manure + Urea significantly increased the rate of photosynthesis followed by the higher amount of food storage and flowering resulting higher yield (Meena et al, 2019).…”
Section: Effect Of the Treatments On Final Mean Fruit Yieldmentioning
confidence: 99%
“…Retamales et al (2008) likewise reported shade netting had little to no effect on air and soil temperature in highbush blueberry. Others, on the other hand, observed that shade netting reduced air and soil temperature in crops such as spinach (Meena et al, 2014) and bell pepper (Dıáz-Peŕez, 2013). The limited effects of shading on temperature in the present study could have been related to the relatively small size of the shading structures, which probably provided enough air circulation underneath to limit temperature gradients.…”
Section: Shade Nettingmentioning
confidence: 99%
“…Shade netting is commonly used to protect agricultural crops from excessive heat and radiation, and in warm climates, has been shown to improve growth and production of highbush blueberry (Lobos et al, 2013;Retamales et al, 2008). The benefit is usually attributed to a reduction of ultraviolet radiation (Lobos and Hancock, 2015), but it could also be related to its effects on air and soil temperature (Dıáz-Peŕez, 2013;Meena et al, 2014).…”
Section: Introductionmentioning
confidence: 99%